Engineering prevascularized composite cell sheet by light-induced cell sheet technology. Issue 52 (26th June 2017) - Zhou, Ying; Dong, Lingqing; Liu, Chao; Lin, Yihan; Yu, Mengfei; Ma, Liang; Zhang, Bin; Cheng, Kui; Weng, Wenjian; Wang, Huiming
Abstract : Light-induced cell sheet technology based on light-responsive TiO2 nanodots film realized an optimal and transferable prevascularized MSC–EC composite cell sheet. Abstract : Early vascularization in bone defects has been considered to play a critical role in the bone regeneration process. Although mesenchymal stem cells (MSCs) co-cultured with endothelial cells (ECs) have attracted the most attention in strategies that seek to achieve vascularized bone, it still remains a challenge to achieve a prevascularized construct in vitro that can be translated conveniently. Here, we provided a strategy of engineering a transferable prevascularized MSC–EC composite cell sheet to promote the vascular-like network formation for bone tissue engineering. We co-cultured human mesenchymal stem cells (hMSCs) and human umbilical vein endothelial cells (HUVECs) on a distinct light-responsive TiO2 nanodots film. Various cell ratios of MSC–EC and culture mediums were explored to achieve the optimal angiogenesis capacity. The prevascularized MSC–EC composite cell sheet was then detached as an intact and confluent cell layer by a simple light treatment, and showed high viability and 3D network formation surrounded by mesenchymal stem cells. This light-induced cell sheet technology therefore realized a novel transferable prevascularized MSC–EC composite cell sheet, and will have a profound impact on further strategies for designing in-bone tissue engineering.